FLAVOUR OF PAPAYA (Carica papaya L.) FRUIT - Hanny Wijaya (BIOTROPIA, 2013)
Papaya is included in five major tropical fruits world production after banana, mango, and pineapple. Indonesia is one of leading country of papaya production after India and Brazil. The Centre of Tropical Fruits Study (PKBT) at Bogor Agricultural University (IPB), Indonesia, has started a long term breeding program since 2003 in order improving the quality of local papayas. Fruit exports are being targeted at more specialized consumers, either those seeking products raised in more environmentally and health-conscious ways or those who are prepared to pay a significant for outstanding flavour. Flavour continues to be the predominant quality characteristic important for a successful international marketing. To understand the biosynthesis pathways are becoming more important for the flavour industry in recent years, as this could aid in the production of the flavour volatiles in the same manner as the natural biosynthesis. It is also necessary to understand the aroma active compounds and their changes during processing because unexpected changes in aroma may cause a product unmarketable even if the other quality factors are acceptable. Understanding the changes of aroma active compounds in the papaya fruit, such as loss of desirable flavour and development of off-flavour during processing will be very helpful for determining proper processing condition. The flavour composition of papaya fruit is reviewed in this paper. This paper will also overview of important publications regarding  the characteristic features of the biology of the fruits, consumption worldwide, commercial application in food processing, though the review of biogenesis of volatiles still be the main focus.  Keywords:  Papaya (Carica papaya L.), flavour, review, volatiles, tropical fruit, biogenesis.